2017
DOI: 10.1371/journal.pone.0183705
|View full text |Cite
|
Sign up to set email alerts
|

2D Ti3C2Tx (MXene)-reinforced polyvinyl alcohol (PVA) nanofibers with enhanced mechanical and electrical properties

Abstract: Novel 2D Ti3C2Tx (MXene)-reinforced polyvinyl alcohol (PVA) nanofibers have been successfully fabricated by an electrospinning technique. The high aspect ratio, hydrophilic surfaces, and metallic conductivity of delaminated MXene nanosheet render it promising nanofiller for high performance nanocomposites. Cellulose nanocrystals (CNC) were used to improve the mechanical properties of the nanofibers. The obtained electrospun nanofibers had diameter from 174 to 194 nm depending on ratio between PVA, CNC and MXen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…It can be seen from Figure a that there is no visible TiO 2 aggregation inside of PVDF nanofibers and no significant differences in roughness between transversal and longitudinal directions. Besides that, the structure of PVDF/TiO 2 nanofiber shown in Figure a is consistent with the previous reports …”
Section: Resultssupporting
confidence: 92%
“…It can be seen from Figure a that there is no visible TiO 2 aggregation inside of PVDF nanofibers and no significant differences in roughness between transversal and longitudinal directions. Besides that, the structure of PVDF/TiO 2 nanofiber shown in Figure a is consistent with the previous reports …”
Section: Resultssupporting
confidence: 92%
“…[204] Moreover, the PPy and Ti 3 C 2 T x layers are in an alternately aligned arrangement. So far, a high number of MXene/polymer composites have been synthesized by solution mixing, such as the T 3 C 2 T x /poly(ethylene oxide), [205,206] T 3 C 2 T x /polyacrylonitrile, [207] T 3 C 2 T x /polyethylene, [208,209] T 3 C 2 T x / poly(vinylidene fluoride), [210] T 3 C 2 T x /polybenzimidazole, [200] T 3 C 2 T x /poly(vinylalcohol), [206,211] etc. [73] In the UV radiation-induced polymerization process (Figure 7e), a mixed sample of MXene power and monomer is stirred under UV light to polymerize the monomer on the surface of MXene.…”
Section: Mxene-polymer Compositesmentioning
confidence: 99%
“…14 In addition, study has indicated that MXenes can be combined with polymers such as PVA and PDDA to create stronger films, which can then be used as electrodes for supercapacitors. 3,4 Another study has taken an approach by sputtering the MAX phase onto a substrate and then exfoliating the Alayer using HF and NH 4 HF 2 to investigate the transmittance of the material in hopes of furthering electronic, photonic, and sensing applications. 15 Table 1 shows the data obtained from these experiments.…”
Section: Electric and Optical Propertiesmentioning
confidence: 99%
“…Specifically, O-terminated MXenes can be used as ammonia (NH 3 ) sensors. 17 A computational study based on O-terminated MXene nanosheet revealed that MXenes with this type of surface functional group are able to selectively and accurately detect NH 3 . The experiments conducted by Lee et al further confirmed that Ti 3 C 2 T x MXenes can be used to detect common volatile organic chemicals such as acetone, ethanol, methanol, and ammonia.…”
Section: Applications As Sensing Devicesmentioning
confidence: 99%
See 1 more Smart Citation